2023
DOI: 10.3390/insects14030231
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Transmission of Plasmodium vivax 210 and Plasmodium vivax 247 by Anopheles gambiae and An. coluzzii, Major Malaria Vectors in Benin/West Africa

Abstract: Current diagnostic and surveillance systems in Benin are not designed to accurately identify or report non-Plasmodium falciparum (Pf) human malaria infections. This study aims to assess and compare the prevalence of circumsporozoite protein (CSP) antibodies of Pf and P. vivax (Pv) in Anopheles gambiae s.l. in Benin. For that, mosquito collections were performed through human landing catches (HLC) and pyrethrum spray catches (PSC). The collected mosquitoes were morphologically identified, and Pf, Pv 210, and Pv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
2
2
1
Order By: Relevance
“…Infection rates for P. vivax in vectors were high in this area, in contrast to previous work in the area according Osse et al [ 13 ] who found 1.5% for one commune in Agbangnizoun in the same region versus 5% in our three study communes. This is likely due to the use of PCR on whole mosquitoes for identification of parasites within the mosquitoes.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Infection rates for P. vivax in vectors were high in this area, in contrast to previous work in the area according Osse et al [ 13 ] who found 1.5% for one commune in Agbangnizoun in the same region versus 5% in our three study communes. This is likely due to the use of PCR on whole mosquitoes for identification of parasites within the mosquitoes.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, the highest infection rate of mosquitoes was observed with P. falciparum , followed by P. vivax (3.3%) and P. ovale (0.4%). These results are similar to those from the work conducted in Cotonou health zones by Poirier et al [ 25 ], and in Benin by Osse et al [ 13 ]. Detection of P. vivax infection had been reported in a large-scale study in asymptomatic subjects in Benin [ 13 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations